Die Arten und Rassen der Anophthalmus schmidti und -mariae Gruppe (Coleoptera: Carabidae: Trechinae) - Daffner, Hermann (Acta entomologica slovenica (Ljubljana), 1998)
The species and subspecies of the Anophthalmus schmidti and A. mariae group are revised. A. bojani sp. n. A. kahleni sp. n. and A. besnicensis frater subsp. n. are described. A. schmidti cordicollis Motschulsky, 1862 is a subspecies incertae sedis. Habitus and male genitalia are illustrated; a key is provided
Keywords: entomologija; hrošči; zoologija; zoology